2011
DOI: 10.1097/dcr.0b013e318223c3d6
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy for Stage III Colon Cancer: Does Timing Matter?

Abstract: Delaying adjuvant chemotherapy in stage III colon cancer beyond 8 to 10 weeks postsurgery appears to be associated with diminished benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 12 publications
5
33
0
3
Order By: Relevance
“…The results showed that patients who started adjuvant chemotherapy within 6 weeks tended to have a higher 5-year DFS rate than those who started it later. This result is similar to that of other studies [24][25][26], reporting that it is beneficial to start adjuvant chemotherapy within 6 weeks after surgery. However, as previous studies and our study show, initiating chemotherapy too early does not guarantee a satisfactory 5-year DFS rate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed that patients who started adjuvant chemotherapy within 6 weeks tended to have a higher 5-year DFS rate than those who started it later. This result is similar to that of other studies [24][25][26], reporting that it is beneficial to start adjuvant chemotherapy within 6 weeks after surgery. However, as previous studies and our study show, initiating chemotherapy too early does not guarantee a satisfactory 5-year DFS rate.…”
Section: Discussionsupporting
confidence: 82%
“…[9]. Numerous studies have reported that patients who start adjuvant chemotherapy 6-8 weeks after surgery have better survival rates than those who do not [24][25][26]. We analyzed the 5-year DFS rates of patients who started chemotherapy within 4 weeks (group 1, 80.26 %), within 4-6 weeks (group 2, 83.03 %), and >6 weeks (group 3, 70.08 %) after resection, but found no differences (p=0.2096).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the proportion of patients who have delayed initiation of CT ranges from 20 to 72 % [5][6][7][8]16]. This is consistent with our data, as approximately one third of patients received adjuvant CT greater than 8 weeks after [10] found that the length of postoperative hospital stay, age, and race were associated with initiating CT more than three months following surgery.…”
Section: Discussionsupporting
confidence: 81%
“…Adjuvant CT has been shown to increase survival in these patients [3,4]. Previous studies have shown that delaying initiation of adjuvant CT greater than 8 weeks after surgical resection adversely affects overall patient survival [5][6][7][8]. A number of demographic, clinical, and systemic factors have been associated with delay in the initiation of CT, including age, race, and postoperative length of stay [9,10].…”
mentioning
confidence: 98%
“…This real-world pattern has previously been reported in the published literature; however, the rates in British Columbia are higher than those reported in other provinces in Canada 8,9 . Comparing retrospective studies is difficult, but the proportion of patients with delayed chemotherapy ranges from 26% in Alberta 11 to 32% in Winnipeg 12 and 35% in Saskatchewan 13 . Although the definition of delayed chemotherapy varies, most studies have accepted fewer than 56 days as the standard against which to judge delay.…”
Section: Discussionmentioning
confidence: 99%